The art and science of natural discovery: Israel Cook Russell and the emergence of modern environmental exploration - Sylvestre, Patrick David, author; Fiege, Mark, advisor; Orsi, Jared P., committee member; Ronda, Bruce A., committee member; Margolf, Diane Claire, committee member (Colorado State University. Libraries, 2008)
Israel Cook Russell was an aesthetically conscious scientist who helped bridge the gap between the late nineteenth-century's scientific explorers, who looked at how nature could best benefit man, and the late twentieth-century's environmental explorers, who looked at how humans could best benefit nature. My thesis argues that Russell's artistic prose and the sympathetic imagery of nature that his prose invoked was essential to the emergence of modern environmental explorers. Furthermore, my thesis argues that modern environmental awareness did not spontaneously emerge in the 1960s. An environmentally conscious sensibility among scientists and naturalists stretches back centuries and was never fully suppressed by the power and influence of economic, commercial, industrial, and political interests. As Israel Russell's generation of scientists, who conducted much of their research directly in nature, gave way to a new era of professional scientists, who conducted most of their research in academic and government laboratories, the reverential relationship between science and nature became less common. Most early twentieth-century scientists may have been more focused on exploring lines of research that were financially supported by imperialist corporations, but scientist's imaginations and awed reactions to nature always remained. Mid to late twentieth-century scientists had similar feelings, but they were more disposed to getting out into the field and experiencing nature firsthand. To help put the ecosystems into context, they looked to the past for inspiration and, eventually, they used science as the means to achieving a new environmental ethic rather than as an instrument of human domination.
Department Head: Ruth M. Alexander.